MOLECULAR GENETICS AND PATHOGENESIS OF CHRONIC MYELOPROLIFERATIVE NEOPLASMS: THE ROLES OF JAK2 V617F, CALR, MPL MUTATIONS, AND THE JAK-STAT PATHWAY - Jakhonov Azizbek Kholmirzaevich; Jakhonov Azizbek Kholmirzaevich (TADQIQOTLAR, 2025)
Abstract: Chronic Myeloproliferative Neoplasms (MPNs) are clonal disorders of hematopoietic stem cells characterized by excessive proliferation of myeloid lineages. The pathogenesis of these disorders is closely associated with somatic mutations in genes that control intracellular signaling. Among these, mutations in JAK2 (V617F), CALR (Calreticulin), and MPL (myeloproliferative leukemia virus oncogene) are the most commonly implicated in BCR-ABL-negative MPNs. These mutations result in constitutive activation of the JAK-STAT pathway, leading to uncontrolled cell growth, survival, and cytokine hypersensitivity. Understanding these genetic alterations is essential for accurate diagnosis, prognosis, and treatment of MPNs. This article provides an in-depth review of the genetic mechanisms underlying MPNs, focusing on the roles of JAK2 V617F, CALR, MPL, and the JAK-STAT signaling pathway, and highlights current and emerging targeted therapies that are shaping modern clinical practice.